Retórica de los sentimientos : etnografías amerindias - Gutiérrez Estévez, Manuel; Surrallés, Alexandre (Tiempo emulado ;, 2015)
"It offers an ethnographic approach to contemporary Amerindian emotions, a winding route that goes from the relationship between perception and affection to class actions, political, cultural recognition, through the study of their rituals and social contexts in general, besides attending in all cases, the link between emotion and textual rhetoric" --Google.